Age-related changes in motor function (I). Mechanical and neuromuscular factors - Wu, R.; De Vito, G.; Delahunt, E.; Ditroilo, M. (International Journal of Sports Medicine, 2020)
This two-part narrative review aims to provide an insight into the age-related mechanical and neuromuscular factors contributing to: (1) decreased maximal muscle strength and power; (2) decreased force control; and (3) increased fatigability. Structural and functional changes from the macro-level of the muscle-tendon unit to the micro-level of the single muscle fibre have been reviewed and are described. At the muscle-tendon unit level, muscle volume, thickness and cross-sectional area, as well as pennation angle and fascicle length all decrease as part of the natural ageing process. These changes negatively affect muscle quality, muscle and tendon stiffness and Young`s modulus and account for impairment in motor performance. A progressive age-related alteration in neuromuscular function is also well-established, with reduction in number and firing rate of the motor unit, contractile velocity and specific tension of muscle fibres, and stability of neuromuscular junction. These could be the result of structural alterations in the: (i) motor neuron, with number reduced, size and collateral sprouting increased; (ii) neuromuscular junction, with decreased post-synaptic junctional fold and density of active zones and increased pre-synaptic branching and post-synaptic area; and (iii) muscle fibre, with decreased number and size and increased type I and co-expression of myosin heavy chain.